Measuring Organizational Culture Influence On Effectiveness Information System Using SEM-PLS: Measuring Organizational Culture Influence On Effectiveness Information System Using SEM-PLS - Cholid Fauzi (Jurnal Mantik, 2020)
Information System (IS) has become essential for organizations to compete in services that focuses on current technology. The resources invested in IS to provide services and generate better value products and as an enabler in implementing good governance. With the model of DeLone McLean, there is an attempt to measure effectiveness of information systems in higher education. Culture of an organization should also be considered as an enabler in the organization's efforts to achieve the desired performance. With the CVF model an IS Success Model, effectiveness could be modeled. The combined model proposed a model of cultural influence on the effectiveness of IS consisting of 6 and 5 constructs effectiveness of the cultural constructs of Information Quality, System Quality, Service Quality, Usage, and Benefits. Cultural self-constructs consisting of clan, adhocracy, market, and hierarchy. Model evaluation is done by using SEM-PLS. The survey was conducted at university by distributing questionnaires to academic staff, faculty, and students. The model has been evaluated with 6 constructs as forming element model. The result model of the influence of culture on the effectiveness of information systems consisting of 6 constructs the effectiveness of Information Quality, System Quality, Service Quality, Usage, Satisfaction and Effectiveness and the 3 constructs of cultural influences namely Clan, Adhocracy and Hierarchy.